Les nouvelles stratégies de communication des organisations publiques, privées et associatives par rapport au déclin des médias généralistes - Marc-François Bernier; François Demers; Alain Lavigne; Charles Moumouni; Thierry Watine (Communication)
In the context of global communication, "traditional" medias are losing their monopoly on public discourse because of the breakthrough of many alternative mechanisms of public expression. Public communication and the public deliberation that accompanies democracies are now dependent on the possibilities and constraints offered by this new and expanding mix of cross media. Pratiques novatrices en communication publique (PNCP), a team of researchers at Laval University is currently conducting an empirical research on that specific question by examining the behaviour of a sample of public, private and associative organizations in matters of communication strategies.